Regular Functions with Values in Ternary Number System on the Complex Clifford Analysis - Ji Eun Kim; Su Jin Lim; Kwang Ho Shon (Abstract and Applied Analysis)
We define a new modified basis i^ which is an association of two bases, e1 and e2. We give an expression of the form z=x0+ i ^z0-, where x0 is a real number and z0- is a complex number on three-dimensional real skew field. And we research the properties of regular functions with values in ternary field and reduced quaternions by Clifford analysis.